Pèleriner, faire du commerce et visiter les lieux saints : Le tourisme religieux sénégalais au Maroc - Nazarena Lanza (L’Année du Maghreb)
Although the Tijaniyya is not very practiced within Morocco anymore, it remains a powerful link between this country and Senegal, where more than half of the population belong to this brotherhood. Many Tijaniyya’s adepts consider the pilgrimage to Fez, the Moroccan town hosting the mausoleum of the brotherhood’s founder, an act of devotion as important as the Hajj to Mecca. This pilgrimage is not new, as it dates back more than a century. However, it is only over the last ten years that it has grown in scope, becoming a major societal phenomenon in Senegal and an important commercial and diplomatic issue for Morocco. This article is based on ethnography of a pilgrimage organized by a Senegalese travel agency, for the Laylatoul-Qadr («Night of Destiny»), in August 2012. The discourses and temporalities that characterize such organized groups of pilgrims, feed particular imaginaries and reveal a multiplicity of dimensions, including social, political and religious dimensions of Senegalese society.The present article emphasizes two aspects: firstly, the meanings and motivations of those travels to Morocco, which allow to understand number of mutations in contemporary Senegalese society (the concept of family, death, belief, leisure, etc.); secondly, the discourses and counter-discourses about the nature of the links between Senegalese and Moroccan peoples, qualified by the governments as «exceptional and fraternal», but which are often differently experienced and reported by many Senegalese residents in Morocco.